1969
DOI: 10.1113/jphysiol.1969.sp008952
|View full text |Cite
|
Sign up to set email alerts
|

Sweat gland function of the donkey (Equus asinus)

Abstract: SUMMARY1. Donkeys sweat on exposure to heat and in response to intravenous adrenaline infusion.2. Thermal sweating was abolished by the adrenergic-neurone blocking agent bethanidine but not by atropine.3. Sympathetic decentralization (by preganglionic sympathectomy) abolished thermal sweating but adreno-medullary denervation had no effect.4. Exercise resulted in sweating from both sympathetically innervated and decentralized skin and from the innervated skin of animals which had previously undergone adreno-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

1971
1971
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 14 publications
3
38
0
1
Order By: Relevance
“…In cattle, regular discharges similar to those seen in sheep occur, but they are superimposed on a continuous output of secretion (McLean, 1963). In the horse and donkey, the output of sweat is also continuous but such fluctuations as occur are less obviously synchronous and are of variable form (Allen & Bligh, 1969;Robertshaw & Taylor, 1969).…”
mentioning
confidence: 92%
“…In cattle, regular discharges similar to those seen in sheep occur, but they are superimposed on a continuous output of secretion (McLean, 1963). In the horse and donkey, the output of sweat is also continuous but such fluctuations as occur are less obviously synchronous and are of variable form (Allen & Bligh, 1969;Robertshaw & Taylor, 1969).…”
mentioning
confidence: 92%
“…). Studies in donkeys have demonstrated that the main component of equid sweat control is neural with the humoral component becoming active during exercise (Robertshaw and Taylor ). Stimulation of sweating in other species can be achieved by cholinergic stimulation, as well as adrenergic stimulation; however, equine sweat glands are insensitive to carbamylcholine and are controlled only by adrenergic neurotransmitters, such as adrenaline and noradrenaline (Johnson and Creed ).…”
Section: Discussionmentioning
confidence: 99%
“…The r e c e p t o r s , however, are of the beta variety (D. Robertshaw, unpublished observations). Under conditions of e x e r c i s e there may also be a humoral component of a d r e n o -m e d u l l a r y origin (Robertshaw and Taylor, 1969b). PROSIMINIAN PRIMATES.…”
Section: Jmentioning
confidence: 98%